The Role Of Financial Stability And Financial Targets In Reducing Fraud In Financial Reporting In Go Green Indonesia Companies (Architecture Image Studies, 2025)
This study aims to analyze the effect of financial stability and financial targets on fraudulent financial reporting (FFR) in Indonesian go green companies, while examining the moderating role of firm size. The research seeks to provide empirical evidence on how financial conditions and managerial pressures influence fraud risk in sustainable firms. The study uses 21 companies listed in the SRI-KEHATI index for the 2016–2023 period, resulting in 168 firm-year observations. Panel data regression analysis was applied through the Fixed Effects Model (FEM) and Moderated Regression Analysis (MRA) to test both direct and moderating effects. The findings show that financial stability significantly reduces the likelihood of FFR, whereas financial targets significantly increase fraud risk. Firm size moderates these relationships by weakening the negative effect of financial stability and strengthening the influence of financial targets on FFR. This research is limited to companies in the SRI-KEHATI index, which may restrict the generalizability of the findings. The use of secondary data also limits the ability to capture qualitative factors influencing fraud behavior. The study contributes to theory by reinforcing the fraud triangle concept, particularly the pressure aspect, while offering novel insights into the moderating role of firm size. For practice, it provides recommendations for companies to maintain stability, set realistic targets, and improve governance, especially in large firms, to minimize fraud risk.